John Lennon's Plastic Ono Band as 'first-person music': notes on the politics of self-expression in rock music since 1970. Issue 3 (December 2020) - Tochka, Nicholas
Abstract: In late 1970, John Lennon began promoting his first post-Beatles solo album, Plastic Ono Band, which he described as 'first-person music' to Rolling Stone editor Jann Wenner. This essay situates the album and two of Lennon's promotional interviews within an emergent politics of individualism in order to explore how self-expression became an aesthetic practice and critical value in rock music. The album's reception and promotion help reveal how key political values – on individualism, rebellion and self-expression – began to be newly articulated to certain kinds of rock musicians after 1970. By understanding that process of articulation, popular music scholars may consider the contradictory political consequences of the broader valorisation of 'first-person music' since the 1970s.